O estudo do movimento eugenio e a compreensão das relações entre ciência e ideologia por professores em formação continuada - Schneider, Eduarda Maria (2013)
The History of Science has allowed our comprehension based on the construction of scientific knowledge as a historical, economical, social, political and ideological undertaking. The discussions about the nature of science are crucial to learn science in a contextualized and critical way according to the different levels of education. Thus, this paper aims at explaining and discussing the relationship between science and ideology as well as emphasizing its importance to teacher training through the following goals: examine Brazilian copies Bulletin concerning Eugenia of 1929 and examine Biology interfaces and eugenics movement and how scientific speech was used to justify ideology of the eugenics movement; evaluate the development of a teaching module on eugenics in a continuing education course for teachers from Paraná State; investigate whether and how teachers perceive the continuing education in science as well as the scientific knowledge permeated by ideology. The research methodology was carried out in two parts: one was based on an analysis of historical documents and the other was based on empirical research with teachers under continuing education. The analysis of historical documents was made by primary sources examination, related to the eugenics movement in Brazil, according to the Discourse Analysis (ORLANDI, 2007) from copies of Eugenia Bulletins published in 1929. Empirical research has investigated the contribution of eugenics movement history in a Brazilian teaching workshop offered to sixteen teachers from the Paraná State Education. The data were recorded by using the following research instruments: initial questionnaire, recordings and transcripts of the discussions that occurred during the didactic workshop and final questionnaire. Reflections concerning the empirical data of this research were also guided by the Discourse Analysis (ORLANDI, 2007). The results from the Bulletins analysis showed how the biological knowledge of that period was used as argumentative elements in defense of the scientific proposal of the eugenics movement to highlight the non-neutrality of science. The analysis of the didactic workshop development pointed out that it allowed to: widen the science teachers’ contextual point of view, especially by understanding how biological knowledge was ideologically used in defense of an eugenic ideal; recognize that the eugenics discourse did not disappear from the global scenario and that it may be present in discourses associated to new genetic technologies. Thus, it is suggested that the inclusion of discussions concerning the History of Science in teachers’ education allows a critical decision-making in relation to scientific knowledge and provides, historically and socially, subsidies for a contextualized Education in Science to demystify the idea of a neutral and linear science.